Activation of peripheral blood and intestinal lamina propria lymphocytes in Crohn's disease. In vivo state of activation and in vitro response to stimulation as defined by the expression of early activation antigens. Issue 6 (June 1987) - Pallone, F; Fais, S; Squarcia, O; Biancone, L; Pozzilli, P; Boirivant, M
Abstract : In the present study the state of activation of either peripheral blood and intestinal lamina propria mononuclear cells in Crohn's disease was defined by investigating the expression of early activation antigens (namely the 4F2 antigen, the transferrin receptor and the interleukin-2 receptor). The expression of 4F2 and T9 antigens was greatly increased--in the peripheral blood and in the intestinal lamina propria whereas the proportion of interleukin-2 receptor bearing cells was much less pronounced. The counts of early activation antigens bearing cells in the lamina propria were quite comparable with those of the autologous peripheral cells. In the peripheral blood counts of 4F2 and T9 positive cells were very high in patients with active Crohn's disease but patients with quiescent disease also had a significantly raised proportion of 4F2 and T9 bearing cells. Only in those patients with no evidence of macroscopic disease (namely those resected without recurrence) the counts of early activation antigens bearing cells were within the normal range. The in vitro mitogen induced expression of early activation antigens on either peripheral and intestinal mononuclear cells of patients with Crohn's disease proved to be both quantitatively and qualitatively similar to that of the controls showing the full expression of 4F2, transferrin receptor, and interleukin-2 receptor. While demonstrating that in Crohn's disease there was no intrinsic defect of generation and expression of growth factors receptors by peripheral and intestinal lymphocytes, these results showed that there was a divergence in the expression of early activation antigens in vivo and in vitro. This would indicate that in Crohn's disease there is an in vivo increased population of preactivated rather than fully activated lymphocytes consisting of 4F2 and T9 bearing cells. The high proportion of these cells in the peripheral blood and in the intestine suggests that a chronic immune activation is present in these patients outside as well as within the affected bowel.